Community Health Worker Use of Smart Devices for Health Promotion: Scoping Review - Merlin Greuel1 , BA, MGH, MD; Frithjof Sy1 , BSc, MD; Till Bärnighausen1,2,3 , MSc, MD, SCD; Maya Adam1,4 , BA, MD; Alain Vandormael1 , MSc, PhD; Jennifer Gates5 , BA; Guy Harling2,6,7,8,9 , BSc, MA, MPH, SCD (My University, 2023)
Background: Community health workers (CHWs) have become essential to the promotion of healthy behaviors, yet their work is complicated by challenges both within and beyond their control. These challenges include resistance to the change of existing behaviors, disbelief of health messages, limited community health literacy, insufficient CHW communication skills and knowledge, lack of community interest and respect for CHWs, and CHWs’ lack of adequate supplies. The rising penetration of “smart” technology (eg, smartphones and tablets) in low- and middle-income countries facilitates the use of portable electronic devices in the field. Objective: This scoping review examines to what extent mobile health in the form of smart devices may enhance the delivery of public health messages in CHW-client interactions, thereby addressing the aforementioned challenges and inducing client behavior change. Methods: We conducted a structured search of the PubMed and LILACS databases using subject heading terms in 4 categories: technology user, technology device, use of technology, and outcome. Eligibility criteria included publication since January 2007, CHWs delivering a health message aided by a smart device, and face-to-face communication between CHWs and clients. Eligible studies were analyzed qualitatively using a modified version of the Partners in Health conceptual framework. Results: We identified 12 eligible studies, 10 (83%) of which used qualitative or mixed methods approaches. We found that smart devices mitigate challenges encountered by CHWs by improving their knowledge, motivation, and creativity (eg, through self-made videos); their status within the community; and the credibility of their health messages. The technology stimulated interest in both CHWs and clients—and sometimes even in bystanders and neighbors. Media content produced locally or reflecting local customs was strongly embraced. Yet, the effect of smart devices on the quality of CHW-client interactions was inconclusive. Interactions suffered as CHWs were tempted to replace educational conversations with clients by passively watching video content. Furthermore, a series of technical difficulties experienced especially by older and less educated CHWs compromised some of the advantages brought about by mobile devices. Adequate CHW training ameliorated these difficulties. Only 1 study (8%) considered client health behavior change as an end point, thus revealing a major research gap. Conclusions: Smart mobile devices may augment CHWs’field performance and enhance face-to-face interactions with clients, yet they also generate new challenges. The available evidence is scarce, mostly qualitative, and focused on a limited range of health outcomes. Future research should include larger-scale interventions across a wide range of health outcomes and feature client health behavior change as an end point.
Keywords: mobile health; community health workers; smart phones; tablets; health promotion; public health; health worker; smart devices; health behaviour; smart technology; health message; health outcome